2017
DOI: 10.1038/s41598-017-13105-9
|View full text |Cite
|
Sign up to set email alerts
|

Denervation-related alterations and biological activity of miRNAs contained in exosomes released by skeletal muscle fibers

Abstract: Exosomes are vesicles released by many eukaryotic cells; their cargo includes proteins, mRNA and microRNA (miR) that can be transferred to recipient cells and regulate cellular processes in an autocrine or paracrine manner. While cells of the myoblast lineage secrete exosomes, it is not known whether skeletal muscle fibers (myofibers) release exosomes. In this study, we found that cultured myofibers release nanovesicles that have bilamellar membranes and an average size of 60–130 nm, contain typical exosomal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…In particular, miR‐206 and miR‐21 have been found to increase in muscle tissue in catabolic/atrophy condition in a mouse model (38). The contribution of muscle atrophy/wasting to the pool of c‐miRs was recently confirmed in exosomes released by myofibers, supporting the conclusion that myofiber‐derived exosomes modulate protein levels of key factors in myogenic or osteogenic differentiation of mesenchymal progenitor cells (39). In particular, miR‐21‐5p was shown to promote the osteogenic differentiation of mouse bone marrow cells by targeting Sprouty homolog 1 (Spryl), negatively regulating the osteogenic differentiation of mesenchymal stem cells (40).…”
Section: Discussionmentioning
confidence: 65%
“…In particular, miR‐206 and miR‐21 have been found to increase in muscle tissue in catabolic/atrophy condition in a mouse model (38). The contribution of muscle atrophy/wasting to the pool of c‐miRs was recently confirmed in exosomes released by myofibers, supporting the conclusion that myofiber‐derived exosomes modulate protein levels of key factors in myogenic or osteogenic differentiation of mesenchymal progenitor cells (39). In particular, miR‐21‐5p was shown to promote the osteogenic differentiation of mouse bone marrow cells by targeting Sprouty homolog 1 (Spryl), negatively regulating the osteogenic differentiation of mesenchymal stem cells (40).…”
Section: Discussionmentioning
confidence: 65%
“…Cell monocultures are a relatively simple system for studying SkM myocyte-derived EVs, but they lack the organization and extracellular matrix characteristic of tissues. Ex vivo incubation of SkM tissue explants has been shown to be an alternative approach to study EVs (1,4,18,25). This method yields EVs with a comparable size, morphology and composition to EVs from cultured cells or blood (1).…”
Section: Background and Rationalementioning
confidence: 99%
“…SkM tissue-derived EVs from obese mice increase expression of genes involved in regulating beta-cell mass in lean recipient mice (18). SkM tissue-derived EVs from hind limb denervated mice alter adipocyte gene expression in a co-culture system (4). In addition to SkM explants, WAT explants have also been studied.…”
Section: Background and Rationalementioning
confidence: 99%
“…In 2017, Gasperi et al reported that skeletal muscle fibers release exosomes. Furthermore, Denervation resulted in a marked increase in miR-206 and reduced expression of miR-1, miR-133 in myofiber-derived exosomes [19]. These findings demonstrate that muscle cells release exosomes which can transfer biologically active miRNAs to recipient cells.…”
Section: Main Textmentioning
confidence: 65%